Epigenetic Regulation of Claudin-1 in the Development of Ovarian Cancer Recurrence and Drug Resistance - Visco, Zachary R.; Sfakianos, Gregory; Grenier, Carole; Boudreau, Marie-Helene; Simpson, Sabrina; Rodriguez, Isabel; Whitaker, Regina; Yao, Derek Y.; Berchuck, Andrew; Murphy, Susan K.; Huang, Zhiqing (Frontiers in Oncology, 2021)
ABSTRACT Approximately 22,000 women are diagnosed with ovarian cancer (OC) in the United States each year and over half that number succumb to this disease annually, often due to recurrent disease. A deeper understanding of the molecular events associated with recurrent disease is needed to identify potential targets. Using genome-scale DNA methylation and gene expression data for 16 matched primary-recurrent advanced stage serous epithelial OCs, we discovered that Claudin-1 (CLDN1), a tight junction protein, shows a stronger correlation between expression and methylation in recurrent versus primary OC at multiple CpG sites (R= -0.47 to -0.64 versus R= -0.32 to -0.57, respectively). An independent dataset showed that this correlation is stronger in tumors from short-term (<3y) survivors than in tumors from long-term (>7y) survivors (R= -0.41 to -0.46 versus R= 0.06 to -0.19, respectively). The presence of this inverse correlation in short-term survivors and recurrent tumors suggests an important role for this relationship and potential predictive value for disease prognosis. CLDN1 expression increased following pharmacologic inhibition of DNA methyltransferase activity (p< 0.001), thus validating the role of methylation in CLDN1 gene inhibition. CLDN1 knockdown enhanced chemosensitivity and suppressed cell proliferation, migration, and wound healing (p< 0.05). Stable CLDN1 knockdown in vivo resulted in reduced xenograft tumor growth but did not reach significance. Our results indicate that the relationship between CLDN1 methylation and expression plays an important role in OC aggressiveness and recurrence. IMPLICATION CLDN1 gene expression and methylation play an important role in ovarian cancer aggressiveness and this relationship may provide a new therapeutic target.